Eco-Theological Community-Based Waste Management For Sustainable Mangrove Ecosystem Conservation In Sinjai Regency - Hardiyanti Ridwan; Srianti Permata; Ibrahim Abdullah; Zaenal Abidin; Satria Ramli; Isma Nawaitul Ihram; Jusrifal Maulana Putra (www.amertainstitute.com, 2026)
Mangrove ecosystems play a vital role in maintaining coastal environmental balance, protecting shorelines from erosion, sequestering carbon, and supporting local economic activities. However, the mangrove area in Tongke-Tongke Village, Sinjai Regency, faces ongoing issues with pollution specifically plastic and household waste that threaten the sustainability of its ecological functions and tourism potential. Consequently, a Community Partnership Program (PKM) titled